A Hospital-based Cross-sectional Study to Assess the Pattern and Trends of Partial Edentulism in BPKIHS and its Teaching Districts - Parajuli, Prakash Kumar; Basnet, Bishal Babu; Limbu, Indra Kumar; Suwal, Pramita (Journal of BP Koirala Institute of Health Sciences, 2020)
Background: Partial edentulism is the state of loss of one or more but not all natural teeth. Edentulism can affect the esthetics of an individual and can have a negative psychological impact. Recording the frequency of partial edentulism and its nature along with its association with different socio-demographic parameters helps to plan the treatment need and goals of the population in that locality. This cross-sectional study was conducted to find out the frequency of partial edentulism among the patients visiting the dental college of BPKIHS and its teaching district hospitals. Methods: Two hundred partially edentulous patients were selected from four hospitals by purposive sampling and their socio-demographic parameters recorded. Intra-oral examination was done to classify partial edentulous spaces according to the Kennedy-Applegate system. Data was analyzed in SPSS version 11.5 and chi-square test was used to determine the association between independent (age-group, gender, socioeconomic status) and dependent variables (number of missing teeth). Results: In both the arches, Kennedy’s class III was the most prevalent type of edentulism. In the maxillary arch, 44.5% had Kennedy’s class III edentulism whereas in the mandibular arch 34.5% had Class III. Kennedy’s class IV was least common (4% in maxillary arch and 6.5% in mandibular arch). Forty-five partially edentulous patients above 50 years of age had ≥ 4 teeth missing and 140 were from medium socio-economic status. Conclusion: Kennedy’s class III partially edentulous arches were the most prevalent type of edentulousness with periodontal disease as major etiology. It was also seen that people with medium socio-economic status were more affected by tooth loss.